การพัฒนาทักษะการอ่านและเขียนสะกดคำภาษาอังกฤษชั้นประถมศึกษาปีที่ 4 โรงเรียนในสังกัดเทศบาลเมืองเลย โดยใช้แบบฝึกทักษะ - เหลาเป, กัมปนาท (วารสารศรีล้านช้างปริทรรศน์, 2019)
บทความนี้มีวัตถุประสงค์เพื่อเปรียบเทียบการพัฒนาทักษะภาษาอังกฤษในชั้นเรียนโดยใช้แบบฝึกทักษะการอ่านและเขียนสะกดคำภาษาอังกฤษ กลุ่มตัวอย่างในการทำวิจัยครั้งนี้คือ นักเรียนชั้นประถมศึกษาปีที่4 โรงเรียนเทศบาล 3 ศรีสว่าง และโรงเรียนเทศบาล 4 ภูบ่อบิด สังกัดเทศบาลเมืองเลย จำนวน 47 คน ในการวิจัยประกอบด้วย แผนการจัดการเรียนรู้โดยการแบบฝึกทักษะการอ่านและเขียนสะกดคำภาษาอังกฤษ จำนวน 1 ชุด คือ ก่อนและหลังการเรียนการสอนโดยใช้เกม ชุดละ 10 ข้อ ทำการวิเคราะห์ข้อมูลโดยหาค่าเฉลี่ย ค่าเบี่ยงเบนมาตรฐานโดยใช้โปรแกรมสำเร็จรูป ผลการศึกษาพบว่า นักเรียนมีคะแนนทดสอบหลังจากการเรียนภาษาอังกฤษโดยการใช้เกมสูงกว่าคะแนนการทดสอบหลังการเรียนโดยไม่ใช้ แบบฝึกทักษะการอ่านและเขียนสะกดคำภาษาอังกฤษ             ผลวิจัยพบว่า การใช้แบบฝึกทักษะการอ่านและเขียนสะกดคำภาษาอังกฤษเพื่อการพัฒนาทักษะภาษาอังกฤษ นักเรียนชั้นประถมศึกษาปีที่ 4 ทำให้ผู้เรียนมีความกระตือรือร้นในการเรียนภาษาอังกฤษได้มากขึ้น และนักเรียนเกิดการพัฒนาทักษะภาษาอังกฤษได้ตามที่ผู้วิจัยคาดหวังไว้ ไม่ว่าจะเป็นการฟัง การอ่าน การพูด และการเขียน ทำให้เด็กเกิดทัศนคติที่ดีต่อการเรียนรู้ภาษาอังกฤษ จึงควรส่งเสริมสนับสนุนให้ครูนำแบบฝึกทักษะการอ่านและเขียนสะกดคำภาษาอังกฤษ เข้ามาใช้ในการเรียนรู้ภาษาอังกฤษ เพื่อให้เกิดการเรียนรู้ที่ดีขึ้น ไม่ใช่จะสอนในตำราเรียนเพียงเท่านั้น             The objective of this study was to compare the development of English language skills in the class by using exercises on reading and spelling in English study of the students learning the English language. The sample in this research. Students in grade four. Thessaban 3 Srisawang school and Thessaban 4 Phu Bo Bidschool belong to Municipal Loei the number 47 people. In this research include Lesson plan by exercises on reading and spelling in English, the number of 1 series is before and after learning the game. Each set of 10 questions. The data were analyzed by the average. Standard deviation by using the program. The study found that the students test scores after learning English by using the game higher test score after learning without use. Exercises on reading and spelling in English. In summary, to use the skill to read and write to the spelling English words to the English language skills development. Students at grade 4, students are eager to learn English and students develop English language skills as researchers expected. Whether it's listening to reading. Speaking and writing, making the baby a good attitude towards learning English should therefore promote the teacher leading the training skills of reading and writing spelling English words. Login to learn English in order to learn better, not to teach in textbooks only.